Executive cognitive ability and business model innovation in start-ups: The role of entrepreneurial bricolage and environmental dynamism - Hou, De'en; Xiong, Aihua; Lin, Chen (Frontiers in Psychology, 2022)
Extant literature suggested that executive cognitive ability is a critical perspective to answering why and how enterprises perform business model innovation. However, the effect of executive cognitive ability on business model innovation is still insufficiently explored. Drawing on entrepreneurial bricolage theory, we developed a moderated mediation model which takes entrepreneurial bricolage as the mediating mechanism and environmental dynamics as the moderating mechanism to explain how executive cognitive ability influences business model innovation. We collected the data of 316 executives of Chinese start-ups through questionnaires for the model test. Results showed that new venture executives' cognitive ability significantly positively affects business model innovation by mediating with entrepreneurial bricolage. Environmental dynamism positively moderates the effect of executives' cognitive ability on business model innovation. Moreover, environmental dynamism positively moderates the mediating role of entrepreneurial bricolage in executive cognitive ability and business model innovation. This study broadens the research scope of entrepreneurial bricolage theory from the perspective of cognitive ability and provides ideas for new ventures' business model innovation.